Impact of Mid-day Meal Scheme on Body Mass Index of School Children in India - Prakasam, Seepana (JOURNAL OF INDIAN EDUCATION, 2019)
This paper is based on the field study conducted on 500 school children studying in Class VI to VIII in Union Territory Chandigarh, to analyse the impact of Mid-day Meal scheme on body mass index. Mid-day Meal scheme has been introduced in India to enhance enrolment, attendance, retention and educational attainment of school going children. A large number of school children belonging to the lower income groups depend on cooked Mid-day Meal. With regards the pattern of consumption of Mid-day Meal, among those who never took and discontinued taking the meal, the proportion of girls is more than that of boys, while in case of continuous consumption, the proportion of boys is more than that of girls. The higher the classes that the children are studying, the lesser the proportion of them availing Mid-day meal. The predominant majority of the children are suffering from under weight (low body mass index); among the underweight children, the proportion of boys is more than that of girls. The larger proportion of children belonging to Below Poverty Line (BPL) category is suffering from low body mass index, when compared to the children belonging to Above Poverty Line (BPL) category. Repetition of more or less same type of food menu should be avoided by enhancing quality to achieve the set objectives of Mid-day Meal scheme.